Legal Protection for Consumers Through Legal Metrology in Trade Activities - Nurcahyo, Edy (Jurnal Pembaharuan Hukum, 2025)
This article aims to analyze the legal protection for consumers through legal metrology in trade activities. Legal metrology plays a crucial role in ensuring fairness in trade, particularly for consumer rights. This study employs a normative legal research method to examine relevant regulations and legal principles. The findings indicate that consumer protection through legal metrology in trade is regulated under the Legal Metrology Law. In every transaction involving measurements, only measuring, weighing, and counting instruments that are certified and guaranteed accurate may be used. Efforts to ensure consumer protection include: 1) providing technical and legal certainty for measuring instruments and their auxiliary tools; 2) enhancing standardization, empowering consumers, supervising the circulation of goods and services, ensuring measurement compliance, and monitoring the quality of goods and services. Consumer protection through legal metrology takes two forms: preventive protection, which focuses on avoiding potential violations, and repressive protection, which provides remedies when violations occur. These efforts are integral to fostering trust and fairness in commercial transactions, ensuring that consumers’ rights are upheld and safeguarded effectively.